A Special Tool for Making a Detail of the T-groove - Sedlak, Josef; Oprsal, Radek; Polzer, Ales; Jaros, Ales; Chladil, Josef (Manufacturing Technology Journal, 2018)
The paper deals with the design of a special machining tool for efficient production of detail on the T-groove of the clamping part. The introductory part of the paper is focused on introducing the Czech company. The practical part of the paper deals with the analysis of the existing state of machining of the clamping body and of the production of the T-groove detail and proposes an innovative solution in the form of more efficient machining process (partial production modification), which consists in the development and production of a special tool with replaceable inserts. The main reason for this partial modification is a significant reduction in unit machine time in the production of the T-groove detail on clamp body parts. Part of the contribution is in the process of streamlining the innovation made in the form of changes to the manufacturing process and the design of the cutting conditions required to produce the T-groove detail on the clamp body parts. The contribution is completed by a technical and economic evaluation, which is related to the analysis and comparison of both proposed production variants in terms of machine times, tool consumption / replaceable inserts and total production costs for the T-groove detail production on the clamp body parts.
Keywords: Special Machining Tool; Production Efficiency; Detail of T-groove; Milling Technology; Innovation; Production Process